2020
DOI: 10.1002/anie.201910297
|View full text |Cite
|
Sign up to set email alerts
|

13.34 % Efficiency Non‐Fullerene All‐Small‐Molecule Organic Solar Cells Enabled by Modulating the Crystallinity of Donors via a Fluorination Strategy

Abstract: Non‐fullerene all‐small‐molecule organic solar cells (NFSM‐OSCs) have shown potential as OSCs, owing to their high purity, easy synthesis and good reproducibility. However, challenges in the modulation of phase separation morphology have limited their development. Herein, two novel small molecular donors, BTEC‐1F and BTEC‐2F, derived from the small molecule DCAO3TBDTT, are synthesized. Using Y6 as the acceptor, devices based on non‐fluorinated DCAO3TBDTT showed an open circuit voltage (Voc) of 0.804 V and a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
139
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(141 citation statements)
references
References 43 publications
2
139
0
Order By: Relevance
“…[ 20 ] However, the small molecule SM1‐F was just reported by Ge et al and named as BTEC‐1F during the preparation of this manuscript. [ 50 ] It was found that the highest occupied molecular orbital (HOMO) energy levels were down‐shifted and the hole mobility of blend films with Y6 acceptor was increased from SM1 to SM1‐S to SM1‐F. In addition, crystallinity and aggregation behavior of the SM donors are influenced by the substituents.…”
Section: Figurementioning
confidence: 99%
“…[ 20 ] However, the small molecule SM1‐F was just reported by Ge et al and named as BTEC‐1F during the preparation of this manuscript. [ 50 ] It was found that the highest occupied molecular orbital (HOMO) energy levels were down‐shifted and the hole mobility of blend films with Y6 acceptor was increased from SM1 to SM1‐S to SM1‐F. In addition, crystallinity and aggregation behavior of the SM donors are influenced by the substituents.…”
Section: Figurementioning
confidence: 99%
“…The other is halogenation, which means to introduce fluorine, chlorine or bromine atoms to the specific positions of some representative units to adjust the energy levels and crystalline properties of the small molecule donor. On the basis of this strategy, several small molecular donors, such as benzodithiophene-Cl (BTR-Cl), BSFTR and BTEC-2F have been developed (see Table 1) and the corresponding OSCs achieve PCEs over 13% when blended with the small molecule acceptor Y6 [28][29][30]. It is well known that variations in morphology induced by the changes in crystallinity and molecular orientation have a significant impact on the performance of OSCs [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the PM6:L11 blend with a µ e,SCLC of 4.3 × 10 −4 cm 2 V −1 s −1 , the PM6:L14 blend shows a higher µ e,SCLC of 6.6 × 10 −4 cm 2 V −1 s −1 , resulting in more balanced mobilities with a µ h,SCLC /µ e,SCLC value of 1.23 and contributing to higher J sc and FF. [39][40] Morphological characterizations of the blend films are performed by atomic force microscopy (AFM), transmission electron microscopy (TEM), and GIWAXS. As shown in Figure S9 (Supporting Information), the height images of two films feature smooth surfaces.…”
mentioning
confidence: 99%